2010
DOI: 10.1519/jsc.0b013e3181e840f3
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Muscle Hypertrophy and Their Application to Resistance Training

Abstract: The quest to increase lean body mass is widely pursued by those who lift weights. Research is lacking, however, as to the best approach for maximizing exercise-induced muscle growth. Bodybuilders generally train with moderate loads and fairly short rest intervals that induce high amounts of metabolic stress. Powerlifters, on the other hand, routinely train with high-intensity loads and lengthy rest periods between sets. Although both groups are known to display impressive muscularity, it is not clear which met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
677
7
82

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 808 publications
(773 citation statements)
references
References 185 publications
(256 reference statements)
7
677
7
82
Order By: Relevance
“…Hormones play an integral role in regulating the anabolic responses to resistance exercise [54]. Elevated concentrations of hormones such as GH, insulinlike growth factor-1 (IGF-1) and testosterone increase the likelihood of hormone receptor interactions that promote anabolic processes [11].…”
Section: Hormonal Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormones play an integral role in regulating the anabolic responses to resistance exercise [54]. Elevated concentrations of hormones such as GH, insulinlike growth factor-1 (IGF-1) and testosterone increase the likelihood of hormone receptor interactions that promote anabolic processes [11].…”
Section: Hormonal Responsesmentioning
confidence: 99%
“…With respect to muscle, it is proposed that cell swelling may trigger the proliferation of satellite cells and facilitate their fusion to hypertrophying muscle fibres [100]. Increased pressure against the cytoskeleton or cellular membrane caused by swelling may be perceived to threaten cellular integrity, causing the cell to initiate a signalling response to reinforce its ultrastructure [46,54,101]. It is suggested that this transient increase in muscle cell volume could activate anabolic signalling cascades, such as mTOR and mitogen-activated protein kinase (MAPK) pathways [12,46,54], which are known to be stimulated by low-intensity resistance exercise with BFR [51,77].…”
Section: Intracellular Swellingmentioning
confidence: 99%
“…Given that hydration-mediated cellular swelling can increase protein synthesis and decrease protein degradation in hepatocytes [33] and a range of other cells [34], it is possible that similar responses occur in muscle cells. Muscle cell swelling may be detected by an intrinsic volume sensor [31], that registers a threat to cellular integrity causing the cell to initiate a signalling response to reinforce its ultrastructure [15,35]. Although a paucity of research has directly examined the downstream signalling events following exercisemediated muscle cell swelling, it is suggested that mammalian target of rapamycin and mitogen-activated protein kinase pathways may be activated [15,31,35], which are known to be important for muscle hypertrophy.…”
Section: Anabolic Effects Of Metabolic Stressmentioning
confidence: 99%
“…O TS é utilizado geralmente por indivíduos bem treinados, que têm como objetivo a hipertrofia muscular, uma vez que este sistema pode produzir um elevado grau de fadiga muscular e estrese metabólico 8 , que são estímulos muito favoráveis para adaptações neuromusculares 9 .…”
Section: Introductionunclassified